2016
DOI: 10.1021/acs.jafc.6b02491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Irradiation on the Nutritional Quality and Cytotoxicity of Apple Juice

Abstract: UV-C irradiation operating at 254 nm wavelength on the polyphenolic and vitamin contents of apple juice including cytotoxicity analysis was studied. UV doses ranging from 0 to 150 mJ·cm were selected for the treatments. Polyphenols (catechin, epicatechin, chlorogenic acid, and phloridzin) and vitamins (riboflavin, thiamine hydrochloride, pyridoxal hydrochloride, pyridoxine, pyridoxamine dihydrochloride, cyanocobalamin, choline chloride, biotin, niacin, and niacinamide) were chemically profiled. It was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
5
34
0
Order By: Relevance
“…Dose verification was not conducted nor was dosage reported by the authors. Consideration of optical attenuation coefficients of the test fluid as wells as verification of UV fluence is fundamentally important to effective inactivation of food borne illnesses in opaque liquid foods (Caminiti et al, ; Islam, Patras, Pokharel, Vergne, et al, ; Unluturk, Atilgan, Baysal, & Unluturk, ). It is quite evident that system design of the continuous flow UV‐C reactor provided adequate mixing that resulted in log 10 linear inactivation of microbes even up to 5 log 10 or more for E. coli and S .…”
Section: Resultsmentioning
confidence: 99%
“…Dose verification was not conducted nor was dosage reported by the authors. Consideration of optical attenuation coefficients of the test fluid as wells as verification of UV fluence is fundamentally important to effective inactivation of food borne illnesses in opaque liquid foods (Caminiti et al, ; Islam, Patras, Pokharel, Vergne, et al, ; Unluturk, Atilgan, Baysal, & Unluturk, ). It is quite evident that system design of the continuous flow UV‐C reactor provided adequate mixing that resulted in log 10 linear inactivation of microbes even up to 5 log 10 or more for E. coli and S .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies with apple juice, the level of polyphenols were relatively stable at a fluence of 40 mJ/cm 2 . In contrast, minor reductions ( P < 0.05) were observed at higher doses (150 mJ/cm 2 ) (Islam et al., ; Islam et al., ). In another study, UV‐C irradiation either increased or did not significantly decrease the polyphenolic content of papaya fruit (Rivera‐Pastrana, Gardea, Yahia, Martínez‐Téllez, & González‐Aguilar, ); therefore, minor changes in the polyphenolic content are predicted when fruits, fruit juices, and tea are treated with UV‐C technology.…”
Section: Resultsmentioning
confidence: 98%
“…UV fluence was quantified based on the log‐reduction of bacteriophage MS2 in the test fluid; a UV fluence of 110 mJ/cm 2 yields a 5‐log reduction. Our previous studies have also demonstrated that MS2 can be used to validate and verify UV fluence in an absorbing fluid; MS2 inactivation has a linear response to UV fluence (Islam et al., ; Islam et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations